Geographic distribution and genetics of killer phenotypes for the yeast Pichia kluyveri across the United States. - Starmer, W T (1992)
Representative strains (n = 61) of the yeast Pichia kluyveri from across the United States were studied for their ability to kill 71 other strains (representing 25 species) of yeast. This survey showed killing activity in 69% of the P. kluyveri strains tested. More extensive analysis of killer activity of 197 P. kluyveri strains against strains of five tester species showed comparable activity (67% of strains tested). This activity was shown to be equally variable within localities, within regions, and across the continent. The genetic basis of the variability was ascertained by tetrad analysis and is most likely due to alleles segregating at three epistatic loci. Evidence for the idea that killer toxins have a role in excluding other yeasts from particular habitats is discussed.